ACTIVE RIGHT-LATERAL STRIKE-SLIP FAULT ZONE ALONG THE SOUTHERN MARGIN OF THE JAPAN SEA - Itoh Y.; Tsutsumi H.; Yamamoto H.; Arato H. (My University, 2002)
We describe an active right-lateral strike-slip fault zone along the southern margin of the Japan Sea, named the Southern Japan Sea Fault Zone (SJSFZ). Onshore segments of the fault zone are delineated on the basis of aerial photograph interpretations and field observations of tectonic geomorphic features, whereas the offshore parts are interpreted from single-/multichannel seismic data combined with borehole information. In an effort to evaluate late Quaternary activity along the fault zone, four active segments separated by uplifting structures are identified in this study. The east-northeast-trending SJSFZ constitutes paired arc-parallel strike-slip faults together with the Median Tectonic Line (MTL), both of which have been activated by oblique subduction of the Philippine Sea plate during the Quaternary. They act as the boundaries of three neotectonic stress domains around the eastern margin of the Eurasian plate: the near-trench Outer zone and NW-SE compressive Inner zone of southwest Japan arc, and the southern Japan Sea deformed under E-W compression from south to north.
Keywords: ACTIVE FAULT ZONE; STRIKE-SLIP FAULT; SOUTHWEST JAPAN; JAPAN SEA; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная